Ages "plomb total" déterminés sur des zircons du Précambrien de la région Frederikshab (côte sud-ouest du Groenland) - Masson, Henri; Chessex, Ronald; Delaloye, Michel (1971)
Zircons contained in five specimens of gneiss from different formations of the Isorssua area (E of Frederikshab, SW Greenland) have revealed the following "total lead" ages: 2755, 2725, 2680, 2630, 2620 Ma. They fit well with the main group of K-Ar ages (2500 to 2700 Ma) known from other localities from the pre-ketilidian basement, but are, however, in average slightly older; this may be explained by the fact that they correspond to an earlier stage of the cooling of the basement and are also less sensitive to later thermal influences. The first two ages (2755 and 2725 Ma) come from non-migmatitic rocks, which are interstratified in the predominantly migmatitic gneiss (2680 to 2620 Ma). The older age of these more refractory rocks results from less complete recrystallisation of the zircons, some inherited material having thus been preserved. The extent of rejuvenation of the zircons therefore appears to depend, thermal conditions being equal, upon the chemical composition of the whole rock. K-Ar ages measured on biotites in the same rocks from the same area approximate 1800 Ma (Larsen, 1966). This discordance is a distant effect of the ketilidian orogeny, which completely rejuvenated the biotites but did not affect the zircons.